Fire on the Mountain: the Bronze and Iron Alpine Ash Altar Material in the Frankfurth Collection at the Milwaukee Public Museum - (:unkn) unknown (My University, 2014)
Milwaukee Public Museum (MPM) Accession 213 is one of many collections orphaned by nineteenth century antiquarian collecting practices. Much of the European prehistoric and early historic material in MPM Accession 213 was collected in a single two-year period from December 1889 to December 1891, but the sudden death of the donor--William Frankfurth--and the passage of a decade between collection and donation left the museum without much context for the materials. Among the artifacts in MPM Accession 213 is a collection of almost 350 metal objects from prehistoric and early historic Europe that have yet to be examined or contextualized. Through archival research and comparative analysis, I demonstrate that the prehistoric metalwork present in this collection comes from one or more of seven identifiable sites--the Grumserbühel, the Sinichkopf, the Segenbühel/Hochbühel, the Fachegg, the Tartscherbühel, the Sonnenburgerbühel, and the Tuiflslammer--all of which have produced evidence of a specific type of prehistoric context called Brandopferplätze [places for burnt sacrifices], also known as Alpine ash altar sites. Alpine ash altar sites offer a unique glimpse into the ritual life of prehistoric European populations because they were in continuous use from the Bronze Age to the Roman period. Using the excavation history of each of these sites, it was possible to narrow down the probable candidates to three of the known sites, as well as at least one unknown Roman site. The artifacts were then categorized and analyzed for presence/absence and degree of damage against existing collections from other Alpine ash altar sites to assess the likelihood of the material coming from this type of context. It was expected that the material profile would closely match the presence/absence of materials from more recently excavated Alpine ash altar sites, and thus provide a foundation for further research into the origins of MPM Accession 213.
Keywords: Alpine Prehistory; Ash Altar; Brandopferplatz; Frankfurth; Ritual